The Epstein-Barr virus and its association with human cancers. Issue 6 (1st December 1999) - Baumforth, K R; Young, L S; Flavell, K J; Constandinou, C; Murray, P G
Abstract : The Epstein-Barr virus (EBV) has been linked to the development of a variety of human malignancies, including Burkitt's lymphoma, Hodgkin's disease, nasopharyngeal carcinoma, some T cell lymphomas, post-transplant lymphoproliferative disease, and more recently, certain cancers of the stomach and smooth muscle. This review summarizes these associations and in particular the role of the viral latent genes in the transformation process.